Discovery of a new radio galaxy within the error box of the unidentified gamma-ray source 3EG J1735-1500 - Combi, Jorge Ariel (2003)
We report the discovery of a new radio galaxy within the location error box of the γ-ray source 3EG J1735-1500. The galaxy is a double-sided jet source forming a large angle with the line of sight. Optical observations reveal a V~18 mag galaxy at the position of the radio core. Although the association with the EGRET source is not confirmed at present because there is a competing, alternative γ-ray candidate within the location error contours, which we also study here, the case deserves further attention. The new radio galaxy can be used to test the recently proposed possibility of γ-ray-emitting radio galaxies beyond the already known case of Centaurus A.